Short term creatine loading without weight gain improves sprint, agility and leg strength performance in female futsal players - Atakan, M. M.; Karavelioglu, M. B.; Harmanci, H.; Cook, M.; Bulut, S. (Science & Sports, 2019)
Objectives: Futsal game requires players to perform frequent bouts of high-intensity activity with limited rest periods that are not sufficient for full recovery. Therefore, creatine supplementation may enhance performance by improving recovery rate. Along with this, the number of studies conducted to determine the effects of creatine on performance in the females is scarce. Thus, the main aim of this study is to identify the effects of short-term (7/day) creatine supplementation on leg strength, velocity and agility in young female futsal players. Equipment and methods: A total of thirty of young female futsal players (aged: 19.83±1.13 years) participated in the study which was designed as randomized and double-blind, on a voluntary basis. Participants were randomly assigned either to creatine (n=15) or placebo (n=15) group. Over 7 days, creatine group received 0.25g/kg/day micronized pure creatine monohydrate (Creapure, Hardline Nutrition, Kavi Gida Istanbul, Turkey) and placebo group did not take any supplements, apart from maltodextrin (Fantomalt, Nutricia, United Kingdom). Before and after 7 days of loading creatine supplementation, body weight, leg strength, velocity and agility performance of the participants were determined. The data obtained were analysed with ANCOVA statistical model. Results: Creatine supplementation significantly improved 10m, 20m and 30m speed performances (P<0.05), leg strength (P<0.05) and agility (P<0.05) in female futsal players. Depending on the creatine loading, however, no significant change in body weight was observed (P>0.05). The data obtained provide that 7 days low dose creatine supplementation may be an effective approach for improving exercise capacity in female futsal players without an associated increase in body weight.